Water, environmental and corporeal traditions in Buddhism - Singh, Anand (Routledge, 2025)
"This book examines ancient Buddhist traditions centered around water. It studies the sustainability and conservation practices of Buddhist monastics and examines how these early practices and ethos are applicable in the contemporary world. The author draws on literary and archaeological sources across cultures and religions to trace the different socio-economic and cultural traditions that utilise water, to formulate a pathway to save water in its purest form. A unique contribution, this book will be an essential read for scholars and researchers of environmental studies, climate change, sustainable development, religious studies, and Buddhist history. It will also be useful to environmentalists and policymakers"--